Investigation of the effectiveness of metformin and various antibiotic combinations against Pseudomonas aeruginosa isolate - Çeylan, Kaan; Zer, Yasemin; Kaya Özen, Gülsüm; Kırkgöz Karabulut, Esra (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Pseudomonas aeruginosa infections are the focus of new treatment alternatives due to their frequent development of resistance to antibiotics and formation of biofilms. Recently, emphasis has been placed on combinations of antibiotics with drugs used for different indications. In this study the combined effects of metformin with imipenem, ceftazidime, cefepim, ciprofloxacin and levofloxacin has been investigated. Methods: 50 P. aeruginosa isolates isolated from patients with cystic fibrosis come to Gaziantep University Microbiology Laboratory were included in the study. The susceptibilities of the isolates to antibiotics were investigated by the liquid microdilution method and the combined effect of metformin and antibiotics by the chequerboard synergy test. Results: In our study, as a result of the chequerboard synergy test; synergy between ceftazidime and metformin 6%, partial synergistic 22% isolates; while no synergistic effect was detected between cefepim and metformin in any isolate, partially synergy 46%; synergy between imipenem and metformin 4%, partial synergy 10%; synergy between ciprofloxacin and metformin 6%, partial synergy 6%, antagonist effect 2%; synergy was detected between levofloxacin and metformin 2% and a partial synergy was detected 12%. Conclusions: This study shows that metformin could be a potential antibiotic in its current form or in different chemical forms to be produced synthetically.